A legitimidade do Minist??rio P??blico para propor a????o civil p??blica em mat??ria tribut??ria - Milhomem, Eduardo Borges (2016)
This paper approaches the legitimacy of the Public Prosecutor's Office to file civil actions in the public interest on tax matters. Regarding such theme, the first subject to be addressed herein shall be the prohibition contained in sole paragraph of Article 1 of the Public Interest Civil Action Act, which prohibits the use of such instrument in claims involving taxes. Such rule, when confronted with the constitutional principle of non-obviation of jurisdiction, in its collective dimension, is deemed as unconstitutional in this paper, because, in such case, a collision of fundamental rights capable of justifying such a restriction of access to the collective action, could not be verified. Along with the legal issue, this research analyzes the precedents of the Supreme Federal Court on the subject, once it was verified that, already in the systematization of general repercussion, the court denied the legitimacy of the Public Prosecutor's Office to file civil actions in the public interest in favor of taxpayers, whereas such actions were admitted when the participation of the Public Prosecutor's Office was in favor of tax authorities. It turns out that after confronting such decision with the specialized doctrine, including previous precedents of the Supreme Federal Court itself, it appears that none of the commands, i.e., the one lacking standing (in the case of actions in favor of taxpayers), and the one with standing (in the case of defense of the tax authorities) should be regarded in a restrictive way, as if worthy of being relativized, because it is necessary to verify, in a concrete case, if there is social interest capable of supporting the legitimacy of the Public Prosecutor's Office. In the case of actions defending taxpayers, such social interest can be demonstrated both by the social dimension inherent to the majority of tax relations and by the broad scope of the claim discussed herein, or even by the taxpayers??? condition. Regarding the demands in favor of tax authorities, although the conclusion is similar, it is more restrictive considering that the legitimacy of the Public Prosecutor's Office shall be characterized only when there is evidence of the existence of primary public interest justifying the actions of the ???parquet???.